Demand for Multi-Year Catastrophe Insurance Contracts: Experimental Evidence for Mitigating the Insurance Gap - Thomas Dudek; Eric R. Ulm; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2021)
People often fail to insure against catastrophes, even when insurance is subsidized. Even when insuring homes, many homeowners still underinsure the full value of their assets. Some researchers have suggested using long-term insurance contracts to reduce these insurance gaps. We examine insurance decisions in a computer-administered experiment that makes several contributions to our understanding of insurance decisions. First, we provide additional evidence showing that many people prefer long-term insurance. Offering this type of insurance may thus increase insurance penetration. Second, we find that underinsurance can result from the reluctance to update the sum insured if there are costs involved with this updating. Long-term insurance contracts that automatically consider price changes over time can thus also deliver a reduction in the insurance gap. Third, we find that once people have made a decision, they tend to repeat it, demonstrating a strong preference for the status quo. Our research suggests that using this status quo bias may allow insurance companies to further increase insurance demand. As previously demonstrated, our results confirm that subsidies are ineffective in increasing insurance penetration.
Keywords: C91; D81; G22; 330; individual decision-making; choice under risk; disaster insurance; underinsurance; status quo; subsidies